Domestic impact of tuberculosis screening among new immigrants to Ontario, Canada - Khan, Kamran; Hirji, M. Mustafa; Miniota, Jennifer; Hu, Wei; Wang, Jun; Chan, Angie; Creatore, Maria I.; Gardam, Michael; Rawal, Sameer; Ellis, Edward; Rea, Elizabeth (Canadian Medical Association journal (CMAJ), 2015)
All Canadian immigrants undergo screening for tuberculosis (TB) before immigration, and selected immigrants must undergo postimmigration surveillance for the disease. We sought to quantify the domestic health impact of screening for TB in all new immigrants and to identify mechanisms to enhance effectiveness and efficiency of this screening. We linked preimmigration medical examination records from 944 375 immigrants who settled in Ontario between 2002 and 2011 to active TB reporting data in Ontario between 2002 and 2011. Using a retrospective cohort study design, we measured birth country–specific rates of active TB detected through preimmigration screening and postimmigration surveillance. We then quantified the proportion of active TB cases among residents of Ontario born abroad that were detected through postimmigration surveillance. Using Cox regression, we identified independent predictors of active TB postimmigration. Immigrants from 6 countries accounted for 87.3% of active TB cases detected through preimmigration screening, and 10 countries accounted for 80.4% of cases detected through postimmigration surveillance. Immigrants from countries with a TB (all-sites) incidence rate of less than 30 cases per 100 000 persons resulted in pre- and postimmigration detection of 2.4 and 0.9 cases per 100 000 immigrants, respectively. Postimmigration surveillance detected 2.6% of active TB cases in Ontario residents born abroad, and TB was detected a median of 18 days earlier in those undergoing surveillance than in those who were not referred to surveillance or who did not comply. Predictors of active TB postimmigration included radiographic markers of old TB, birth country, immigration category, location of application for residency, immune status and age. Universal screening for TB in new immigrants has a modest impact on the domestic burden of active TB and is highly inefficient. Focusing preimmigration screening in countries with high incidence rates and revising criteria for postimmigration surveillance could increase the effectiveness and efficiency of screening.